2018
DOI: 10.1097/meg.0000000000001190
|View full text |Cite
|
Sign up to set email alerts
|

Screening of hepatitis C virus infection in adult general population in Spain

Abstract: HCV screening strategies applied to the general population are good means to diagnose and treat patients who are not aware of their infection, avoiding new transmissions as well as disease progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0
5

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 21 publications
1
11
0
5
Order By: Relevance
“…A study on 2637 individuals in Valencia, Spain, found that antibody detection was positive in 30 individuals (1.1%). The study showed that among the anti-HCV-positive cases, 23.3% had tattoos and piercing as a risk factor, as in the present study, although there is no representation regarding the decade of birth 17 . A survey of 2,128 individuals in Suriname found an association between HCV positivity and male sex, advanced age, Javanese ethnicity, and presence of tattoos 22 .…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…A study on 2637 individuals in Valencia, Spain, found that antibody detection was positive in 30 individuals (1.1%). The study showed that among the anti-HCV-positive cases, 23.3% had tattoos and piercing as a risk factor, as in the present study, although there is no representation regarding the decade of birth 17 . A survey of 2,128 individuals in Suriname found an association between HCV positivity and male sex, advanced age, Javanese ethnicity, and presence of tattoos 22 .…”
Section: Discussionsupporting
confidence: 58%
“…the great epidemic of intravenous drug use in the 1980s in Spain, as well as in Brazil several years later, which was later than that in the USA and other European countries 17 . In the USA, there is a new boom; a majority of patients who were infected after 2009 reported injection drug use (IDU) (40.6%) as their source of infection, which coincides with the recent heroin use epidemic 18 .…”
Section: Discussionmentioning
confidence: 96%
“…Similar data regarding hepatitis C prevalence have been reported in two recent studies conducted in other regions in Spain. One in Valencia in 2018 found an HCV seroprevalence of 1.14% and another in Navarra from 2014–2016 obtained an HCV seroprevalence 0.83%. However, the methodology in these studies differed from ours, as the first was performed only in an adult population between 25 and 70 years of age in a small area, and the second was undertaken in patients admitted for elective surgery.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the study has unmasked several individuals with chronic HCV infection that did not define themselves as belonging to known risk groups. A recent Spanish pilot study for an eventual population-based screening program included the adult population (20-75 years) in a small health area with a participation rate of 46.2% (2637/5706) [39]. HCV RNA was detected in 13 persons (0.5%), of whom five were unaware of the disease.…”
Section: Screening Strategies In a Low-prevalence Area: Whom And How mentioning
confidence: 99%